Medical and information technologies converge. - Cohen, T. (IEEE Engineering in medicine and biology magazine)
Information technology offers medical science tools to collect, process, store, and communicate clinical data. Healthcare institutions have adapted standards-based data communication technologies that allow easy implementation of communications infrastructure. As clinical and information technologies have converged, two trends have emerged: the widespread use of commercial off-the-shelf hardware and software and the use of standards-based communication technologies. Technical support for these complex systems requires an integrated, "end-to-end" view and staff who are knowledgeable of both clinical and computer technologies. In this article, examples of new computerized medical devices are discussed as well as the support and support staff implications of the ever-growing influence of IT on clinical systems.